Therapeutic Effects of Mesenchymal Stem Cells Expressing Erythropoietin on Cancer-Related Anemia in Mice Model - Estiri, Mohammad; Estiri, Bahareh; Fallah, Asghar; Aghazadeh, Marziyeh; Sedaghati, Amir; Abdollahi, Abbas; Rabienia, Mahsa; Mortazavidehkordi, Nahid; Farjadfar, Akbar (Current Gene Therapy, 2022)
Background: Cancer-related anemia (CRA) negatively influences cancer patients’ survival, disease progression, treatment efficacy, and quality of life (QOL). Current treatments such as iron therapy, red cell transfusion, and erythropoietin-stimulating agents (ESAs) may cause severe adverse effects. Therefore, the development of long-lasting and curative therapies is urgently required. Objective: In this study, a cell and gene therapy strategy was developed for in vivo delivery of EPO cDNA by way of genetic engineering of human Wharton’s jelly mesenchymal stem cells (hWJMSCs) to produce and secrete human EPO protein for extended periods after transplantation into the mice model of CRA. Methods: To evaluate CRA’s treatment in cancer-free and cancerous conditions, first, a recombinant breast cancer cell line 4T1 which expressed herpes simplex virus type 1 thymidine kinase (HSV1-TK) by a lentiviral vector encoding HSV1-TK was developed and injected into mice. After three weeks, all mice developed metastatic breast cancer associated with acute anemia. Then, ganciclovir (GCV) was administered for ten days in half of the mice to clear cancer cells. Meanwhile, another lentiviral vector encoding EPO to transduce hWJMSCs was developed. Following implantation of rhWJMSCs-EPO in the second group of mice, peripheral blood samples were collected once a week for ten weeks from both groups. Results: Analysis of peripheral blood samples showed that plasma EPO, hemoglobin (Hb), and hematocrit (Hct) concentrations significantly increased and remained at therapeutic for >10 weeks in both treatment groups. Conclusion: Data indicated that rhWJMSCs-EPO increased the circulating level of EPO, Hb, and Hct in both mouse subject groups and improved the anemia of cancer in both cancer-free and cancerous mice.
Keywords: erythropoietin